STRATEGI PENINGKATAN KINERJA PEGAWAI NEGERI SIPIL BIDANG PRASARANA TRANSPORTASI DINAS PERHUBUNGAN KABUPATEN PACITAN (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The performance condition of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office still needs to be optimized, because there are several things that deviate from their duties and functions. This research is qualitative research. The purpose of the study is to identify the performance of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office that has not been optimal, identify the factors causing the performance of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office has not been optimal and to formulate strategies to improve the performance of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office. The cause of the performance of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office has not been optimal because employee competence is still low, lack of knowledge at work, limited infrastructure, lack of discipline at work, employees who are reluctant to continue S1, lack of understanding of changes in Government Regulations. The performance assessment of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office is good with an average value of 2.77, but when viewed from each element, there are still things that need to be developed, namely elements of knowledge about work, creativity and independence. Strategies to improve the performance of Civil Servants in the Transportation Infrastructure Sector of the Pacitan Regency Transportation Office, according to the SWOT analysis, are (1) Alternative SO Strategies with continuous guidance from the government and increasing employee participation in education and training activities (2) Alternative WO Strategies by means of sustainable coaching and improving employee competence (3) Alternative ST Strategy by approaching the community and following the socialization of government regulations in the field of transportation (4) Alternative ST Strategy by increasing employee discipline and improving infrastructure.Kondisi kinerja Pegawai Negeri Sipil Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan masih perlu dioptimalkan, karena terdapat beberapa hal yang menyimpang dari tugas dan fungsinya. Penelitian ini merupakan penelitian kualitatif. Tujuan Penelitian adalah untuk mengidentifikasi kinerja Pegawai Negeri Sipil Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan yang belum optimal, mengidentifikasi faktor-faktor penyebab kinerja Pegawai Negeri Sipil Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan belum optimal dan untuk merumuskan strategi guna meningkatkan kinerja Pegawai Negeri Sipil Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan. Penyebab Kinerja Pegawai Ngeri Sipil  Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan belum optimal karena kompetensi pegawai masih rendah, kurangnya pengetahuan dalam pekerjaan, sarana prasarana yang terbatas, kurang disiplin dalam bekerja, pegawai yang enggan melanjutkan S1, kurangnya pemahaman perubahan Peraturan Pemerintah. Penilaian kinerja Pegawai Negeri Sipil di Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan sudah baik dengan nilai rata-rata 2,77, namun apabila ditinjau dari tiap unsurnya masih ada yang perlu dikembangkan kinerjanya yaitu unsur pengetahuan tentang pekerjaan, kreativitas dan kemandirian. Strategi peningkatkan kinerja Pegawai Negeri Sipil di Bidang Prasarana Transportasi Dinas Perhubungan Kabupaten Pacitan, menurut analisis SWOT adalah (1) Alternatif Strategi SO dengan pembinaan berkelanjutan dari pemerintah dan meningkatkan keikutsertaan pegawai dalam kegiatan pendidikan dan pelatihan (2) Alternatif Strategi WO dengan cara pembinaan berkelanjutan dan peningkatkan kompetensi Pegawai (3) Alternatif Strategi ST dengan melakukan pendekatan kepada masyarakat dan mengikuti sosialisasi regulasi pemerintah di bidang perhubungan (4) Alternatif Strategi ST dengan meningkatkan kedisiplinan Pegawai dan peningkatan sarana prasarana.
Keywords: Performance; Employees; Discipline; Competence; Infrastructure